The need for Shari'ah-compliant awqāf banks - Hanan Gabil; Benaouda Bensaid; Tahar Tayachi; Faleel Jamaldeen (Journal of Risk and Financial Management, 2020)
Bridging global economic inequalities calls for effective financial alternatives such as awqāf banks to better attend to the needs of the poor and underprivileged. This is expected to address the root causes of poverty and ensuing economic gaps, improving much of the living standards whether pertaining to education, health, shelter, employment or basic social services while reducing the state's economic and financial burden. We envision awqāf banks as institutions which are established through cash awqāf and which operate multiple awqāf funds alongside an assortment of financial instruments. The main use of their awqāf funds are the issue of low-cost credit to the poor, economically disadvantaged and underprivileged, instead of focusing solely on generating and maximizing shareholder profits. This is to support the economy through of steady and sustainable growth, effectively raising the lower bar on per capita income and lifting multitudes out of poverty and need. This paper explores how low-cost credit can be provided to the poor or lower income demographics through awqāf banks, while addressing relevant issues such as Shari'ah compliance, services rendering, investment and awqāf distribution. This paper also examines current studies on awqāf in relation to finance and banking, the basic functions, and characteristics of the Shari'ah-compliant awqāf bank, as well as evaluations of awqāf banks. Current studies show that there is a legitimate need for Shari'ah-compliant awqāf banks which not only providing services for its beneficiaries but also manage investments and awqāf funds that contribute to overall national development and economic growth. This study would be of high relevance to experts, practitioners, financial managers, regulators, and policy makers in the fields of awqāf, banking and finance.
Keywords: 330; awqāf bank; awqāf management; cash awqāf; Islamic Endowment